1990
DOI: 10.1002/pen.760301307
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility studies in blends of polybenzimidazoles and poly(4‐vinyl pyridine)

Abstract: 1 1 201Poly[2,2'-(m-phenylene)-5.5'-bibenzimidazole] (PBI) is shown to be miscible with poly(4-vinyl pyridine) over the entire composition range. Experiments were performed with commercial PBI as well as a lower molecular weight material synthesized by us. Blend miscibility is evidenced by single glass transition temperature intermediate between the pure polymers. Hydrogen bonding between the components was detected by infrared spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…An artificial IR spectrum of the mixture of the blend components was simulated in software provided with the Perkin-Elmer instrument as depicted in Q. 5. The Ar value of 1597 cm-' peak calculated for this artificial mixture was found to be 0.056.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial IR spectrum of the mixture of the blend components was simulated in software provided with the Perkin-Elmer instrument as depicted in Q. 5. The Ar value of 1597 cm-' peak calculated for this artificial mixture was found to be 0.056.…”
Section: Resultsmentioning
confidence: 99%
“…Ho, Wu, and Su (4) have reported the partial crosslinking of blends of polystyrene and styrene butadiene rubber (SBR) during Brabender mixing at 200°C due to reaction of vinyl group with polymeric radicals generated by mechanical degradation of SBR. Makhija, et al (5) have studied the miscibility of polybenzimidazoles with poly (4-vinyl pyridine) and found that they are compatible over all composition range and the compatibility has been 'To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…4 Mechanical and thermal properties of the blends exhibited gross synergism in their blend characteristics. 3,5 In general, miscibility can be achieved by specific interaction between the blend constituents such as hydrogen bonding, [6][7][8][9] ion -dipole interaction, 10 dipole -dipole interaction, 11 and chemical reaction 1,2,[12][13][14][15][16][17][18] between the blend constituents due to the fact that they are usually governed by a negative free energy of mixing, i.e., ⌬Gm ϭ ⌬H Ϫ T ⌬ S Ͻ 0 ⌬Gm ϭ change in free energy of mixing T ϭ absolute temperature That means that either ⌬H, the heat of mixing, should be negative or ⌬S, the entropy of mixing must be higher as compared to ⌬H.…”
Section: Reactive Blendingmentioning
confidence: 99%
“…However, it is difficult to process due to its high melting temperature and limited solubility 6. Many modification methods have been employed to solve these disadvantages of PBI 7–19. Modification of the structure of PBI to impart solubility without sacrificing the desirable properties has been the focus of a lot of research work 11, 20–23.…”
Section: Introductionmentioning
confidence: 99%